Déclencher, représenter, restituer : le théâtre comme méthode géographique - Lise Landrin (Unité Mixte de Recherche 8504 Géographie-cités, 2019)
What methods do geographers have today to engage in participatory fieldworks? With the renewal of postcolonial and feminist scientific discourses, creative methods have emerged to generate alternatives to the construction of the ‘Other’. Tough the creative turn is diverse; it is surprising not to see the theatre integrating the geographers’ toolboxes. This shadow area is even more surprising when we think about the fact that every spatial interaction is shaped by roles. Theater, as an expressive practice of bodies and loosed voices, opens the door for a new discursive regime. This article questions the advantages of a participative fieldwork method based on the "triggering theater": an artistic practice that open a path for another production of knowledge. Using triggering theatre in a collaborative research with a nepali comedian, I want to show how scientific productions can include transformation of social constraints through the mediation of the stage. This article first presents the epistemological renewal putting theater as a geographical tool. Then, it details the terms of an experimental protocol, before discussing the results of a shared reflexivity in rural Nepal between March 2017 and May 2018.